The impacts of hospital admission in very late‐onset schizophrenia‐like psychosis: A case report - Shigeki Katakami; Yuto Satake; Takashi Suehiro; Daiki Ishimaru; Erina Nakanishi; Hideki Kanemoto; Kenji Yoshiyama; Manabu Ikeda (PCN Reports)
Abstract Background Very late‐onset schizophrenia‐like psychosis (VLOSLP) is a psychotic disorder with an age of onset ≥60 years, and social isolation is a risk factor. Reports on the impact of interventions for isolation and loneliness on psychiatric symptoms in VLOSLP are limited. Case Presentation An 87‐year‐old woman, widowed and living alone, developed psychosis, including paranoia, erotomania, and visual hallucinations, at 84 years old during a period when her interactions with others were limited by the COVID‐19 pandemic and osteoarthritis. She was eventually brought to our hospital with a local dementia outreach team. She was admitted and diagnosed with VLOSLP with mild cognitive decline through imaging and neuropsychological tests confirming the absence of dementia. Immediately after admission, her psychotic symptoms became inactive. She was transferred to another psychiatric hospital to prepare for her move to a long‐term care facility because her psychosis was alleviated. During admission, she enjoyed the company of others and occupational therapy, and her score on the UCLA Loneliness Scale Version 3 improved from 44 at admission to 35 at discharge. Conclusion The admission itself improved the patient's psychosis, which seemed to be related to the alleviation of isolation and loneliness.